Identifikasi, Intensitas dan Persentase Serangan Hama Helopeltis sp. (Hemiptera: Miridae) pada Acacia mangium Willd. - Sucahyono, Muhamad Pangky (Jurnal Agro Teknologi Tropika, 2013)
One of the problems in the management of Acacia mangium is Helopeltis sp. infestation. Current research andreport on Helopeltis sp. as the pest on A. mangium are not much, so it is necessary to identify this pest and itâs damagelevel. The research aims to identify the spesies of Helopeltis on A. mangium and to observe the intensity and percentageof their infestation. Identified Helopeltis sp. was taken from A. mangium plant in the field. The identification was held inthe laboratory. The intensity and percentage of infestation conducted in three different locations on 1, 2, 3, 4, 5, and 6months old plantation. The plot unit samples were taken with transect line methods. The observation of the damage wasevaluated by giving the score for each plant according to itâs severity. Helopeltis sp. that giving A. mangium is H.theivora, with intensity and percentage of infestation on 6 months was 56.55% and 100%. The intensity and percentageof infestation of H. theivora on the A. mangium decreased from 3 months to 6 months on plants.Keywords: Identification, intensity of infestation, percentage of infestation